Understanding How User-Generated Content and Viral Marketing Drive Tumblers Purchase Decisions Among Gen Z: The Mediating Role of Sustainable Marketing - Arsyva Levina; Donni Junipriansa; Alma Syifa Maulidina (Dinasti Publisher, 2026)
This study aims to analyze the influence of user-generated content and viral marketing on Generation Z’s purchasing decisions regarding Stanley tumblers in Indonesia, with sustainable marketing as a mediating variable. This study is done based on the increasing role of social media in shaping consumption behavior and the importance of sustainability values in purchasing decisions. A quantitative approach is applied using a cross-sectional design and purposive sampling technique involving 100 respondents who had been exposed to Stanley tumbler content on TikTok. The data collected through questionnaire and analyzed by using statistical analysis techniques. The results indicate that user-generated content and viral marketing have a positive and significance influence on purchasing decisions, both directly and through sustainable marketing. Furthermore, sustainable marketing strengthen the relationship between digital marketing stimuli and purchading decisions. This study conclude that the integration of digital content and sustainalbility values is a key factor in influencing Gen Z consumers’ purchasing decisions.